Enhanced dielectric properties and energy storage of the sandwich-structured poly(vinylidene fluoride-cohexafluoropropylene) composite films with functional BaTiO3@Al2O3 nanofibres. Issue 3 (2019) - Zha, Jun-Wei; Yao, Shi-Cong; Qiu, Yan; Zheng, Ming-Sheng; Dang, Zhi-Min
No abstract available